EFFECTIVENESS OF SMALL-GROUP INSTRUCTION METHOD ON PUPIL’S ACHIEVEMENT IN ELEMENTARY NUMBER LINE CONCEPTS IN AWKA SOUTH LOCAL GOVERNMENT AREA OF ANAMBRA STATE - Umeji Ifeoma Chinyere (Adisam Publisher, 2025)
This study examines the effectiveness of the small-group instruction method on pupil's achievement in elementary number line concepts, employing a quasi-experimental design. The research investigates whether the implementation of small-group instruction enhances pupils' understanding and proficiency in number line concepts compared to teacher- centered instruction method. The study involved a sample of 140 elementary school pupils from selected schools within the Awka South Local Government Area. The instrument for data collection was Number Line Achievement Test (NLAT). The experimental group received instruction through small-group settings, while the control group received the standard whole-class teacher-centered instruction method. Pre-test and post-test measures were administered to both groups to assess their achievement in number line concepts. The collected data were analyzed in Statistical Package for the Social Sciences (SPSS) using the mean and standard deviation. T-test statistics was used to test the research hypotheses at 0.05 level of significance. The results showed that pupils taught elementary number line concepts using small-group instruction method achieved higher scores than those taught using teacher-centered instruction method. The findings of the study provide insights into the impact of small-group instruction on pupil's achievement in elementary number line concepts and offer practical implications for instructional practices in primary education studies. The results contribute to the existing body of knowledge on effective teaching methods for enhancing pupils' mathematical understanding and suggest recommendations for further research and implementation of small-group instruction in the teaching of number line concepts.